Soil reinforcement by Robinia pseudoacacia roots and its stabilization mechanism for shallow root-soil composite slopes - Xing Chen; Yanjun Shen; Ping Ni; Zijian Li; Jinyu Zhu; Yibing Ning; Haitao Wang (Bulletin of Engineering Geology and the Environment, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Failure mechanism and damage assessment of talus slopes with varied gradation under seismic loading - Xing Wei; Shitao Cheng; Rui Chen; Xinle Zhai; Jun Feng; Zijian Wang; Yanjun Li; Le Cheng (Landslides, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

Unraveling shallow landslides in the Qinling Mountains: Novel insights into vegetation-hydrology driven mechanisms - Xing Chen; Yanjun Shen; Yibing Ning; Bailei Shi; Jinyu Zhu; Sirui Li; Zijian Li; You Lyu; Jianbing Peng (Journal of Mountain Science, 2026)

Characteristics and mechanism of high-vegetation-coverage recurrent debris flow disaster chain: Insights from a case in the Qinling Mountains, China on July 19, 2024 - Jinyu Zhu; Yanjun Shen; Yibing Ning; Jianbing Peng; Xing Chen; Bailei Shi; Shengwei Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Formation of the Da'anhe reduced gold skarn in NE China: Evidence from U-Pb geochronology, and whole-rock and mineral geochemistry - Litian Zhang; Qihai Shu; Kai Xing; Fan Yu; Yanjun Wang; Zhonghai Zhao; Bing Li; Qingfei Wang; Jun Deng (Lithos, 2025)

The hominin teeth from the late Middle Pleistocene Hualongdong site, China - Xiujie Wu; María Martinón-Torres; Song Xing; Shuwen Pei; Yanjun Cai; Haowen Tong; José María Bermúdez de Castro; Wu Liu (Journal of Human Evolution, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Corrigendum to “Complete biosynthesis of the potential medicine icaritin by engineered Saccharomyces cerevisiae and Escherichia coli” [Sci. Bull. 66(18) (2021) 1906–1916] - Pingping Wang; Chaojing Li; Xiaodong Li; Wenjun Huang; Yan Wang; Jiali Wang; Yanjun Zhang; Xiaoman Yang; Xing Yan; Ying Wang; Zhihua Zhou (Science Bulletin, 2025)

The performance of an embankment over soft clay under rainfall with tension cracks at soil-pile interface caused by lateral deformation - Xing Wei; Shitao Cheng; Yanjun Li; Rui Chen; Zijian Wang; Fan Tang; Bingkun Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Why are the Qinling Mountains Significant to China? - Xing Chen; Yanjun Shen; Qingyi Mu; Panpan Xu; Fenghao Duan; Jianbing Peng (Journal of Earth Science, 2025)

Enhanced co-pyrolysis of textile and leather waste with Ca/Fe-enriched sludge ash: Catalytic effect on thermal behavior, volatile composition, and biochar formation - Yanjun Hu; Zhipeng Xia; Xu Wang; Bo Xing; Qi Chen; Fan Yu; Nan Zhou (Fuel, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Historical trends and pollution assessment of heavy metals in core sediments from the Jiangsu offshore area, China - Li He; Shenghui Jiang; Xuhui Chen; Haiyan Cheng; Peng Ye; Lu Chen; Yuan Liu; Yanjun Yin; Xing Leng (Regional Studies in Marine Science, 2023)

Interfacial permeation preparation of ZIF-8 in reactive deep eutectic for efficient adsorption and selective removal of Congo red - Yiwen Li; Huanhuan Zhang; Shikuan Xu; Yangyang Wang; Qi Guo; Rong Li; Yanjun Xing (Journal of Environmental Chemical Engineering, 2023)

Morphological and morphometric analyses of a late Middle Pleistocene hominin mandible from Hualongdong, China - Xiujie Wu; Shuwen Pei; Yanjun Cai; Haowen Tong; Ziliang Zhang; Yi Yan; Song Xing; María Martinón-Torres; José María Bermúdez de Castro; Wu Liu (Journal of Human Evolution, 2023)

Heavy metal concentration profiles and pollution assessment in the Jiangsu offshore area, China - Lihui Xiang; Shenghui Jiang; Haiyang Cheng; Yanfen Wang; Qiang Liu; Yanjun Yin; Xing Leng (Marine Pollution Bulletin, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

Seismicity induced by geological CO2 storage: A review - Yuxiang Cheng; Wenna Liu; Tianfu Xu; Yanjun Zhang; Xinwen Zhang; Yunyan Xing; Bo Feng; Yi Xia (Earth-Science Reviews, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Do behavioural interventions enhance waste recycling practices? Evidence from an extended meta-analysis - Ziqian Xia; Yanjun Gu; Jiangnan Li; Jinliang Xie; Fangyi Liu; Xing Wen; Xi Tian; Chao Zhang (Journal of Cleaner Production, 2023)

The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Guorong Zhong; Xuegang Li; Jinming Song; Baoxiao Qu; Fan Wang; Yanjun Wang; Bin Zhang; Detong Tian; Jun Ma; Huamao Yuan; Liqin Duan; Ning Li; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO 2 flux. However, the influence of the long-standing greater CO 2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean p CO 2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO 2 flux difference from 0.41 PgC yr -1 in 1992 to 0.73 PgC yr -1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO 2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO 2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO 2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)